IMPLEMENTASI PRINSIP MEMPERSUKAR PERCERAIAN DALAM MENEKAN TINGGINYA ANGKA PERCERAIAN DI PENGADILAN AGAMA SOREANG - Noval Aditya; Ahmad Damiri; Ahmad Maula Hadi (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The high divorce rate in the Soreang Religious Court raises fundamental questions about the extent to which the principle of making divorce difficult as mandated by Law Number 1 of 1974 can be effectively implemented by judges. Previous studies have discussed the factors causing divorce and the relevance of the principle of making divorce difficult from an Islamic legal perspective, but there has been no research that empirically examines the strategies and concrete efforts of judges in operationalizing this principle amidst the high divorce rate, particularly in the Soreang Religious Court. This study aims to fill this scientific gap by examining the implementation of the principle of making divorce difficult through Grindle's policy implementation theory approach, which has not been applied in similar research contexts. This study uses an empirical juridical approach and is a field study. Primary data were obtained through interviews with judges at the Soreang Religious Court, while secondary data came from official documents of the Soreang Religious Court, Law Number 1 of 1974, SEMA, and several other literature reviews such as books, articles, and others to support the primary data. The findings of this study indicate that the Soreang Religious Court's application of the principle of making divorce difficult is ineffective, hampered by the absence of many defendants in court, thus hindering the efforts to reach a settlement. Furthermore, inter-institutional cooperation is needed to make this principle of making divorce difficult more effective.